How far from the tree does the apple fall?: field training officers, their trainees, and allegations of misconduct - Getty, Ryan M. (Crime & delinquency, 2016)
Grounded in both organizational- and individual-level theories, this study examined the relationship between police field training officers (FTOs) and their trainees’ subsequent allegations of misconduct. Trainees in the sample were each exposed to multiple FTOs, which presented a unique methodological problem. As such, multilevel models that permitted the nesting of individual trainees within multiple higher order groups of FTOs were estimated. Results revealed that approximately one quarter of the variation in trainees’ allegations of postsupervision misconduct was attributed to FTOs, suggesting the apple (trainee) indeed falls close to the tree (FTO). Implications for FTO selection and training are discussed.